MIGRAINE AS A NEUROINFLAMMATORY DISEASE: PATHOPHYSIOLOGY, TREATMENT, AND IMPACT OF PHYSICAL EXERCISE - Agnieszka Ozdarska; Agnieszka Floriańczyk; Ewa Romanowicz; Aleksandra Kołdyj; Adrian Krzysztof Biernat; Marcin Lampart; Anna Rupińska; Kamila Krzewska; Hanna Skarakhodava (International Journal of Innovative Technologies in Social Science, 2025)
Migraine is a common and disabling neurological disorder now recognized as a neuroinflammatory condition. Its pathophysiology involves interactions between neurons, glial cells, vascular structures, and immune pathways, with critical roles played by pro-inflammatory cytokines, CGRP signaling, microglial activation, and mitochondrial dysfunction. These factors contribute to pain sensitization and chronic inflammation in the brain. This review summarizes current understanding of migraine as a neuroinflammatory disease, examining both pharmacological and non-pharmacological treatment strategies. Acute therapies include NSAIDs, triptans, and CGRP antagonists, while preventive options involve antiepileptics, beta-blockers, and monoclonal antibodies targeting CGRP. Beyond medications, lifestyle factors such as stress, sleep disorders, poor diet, and gut dysbiosis are shown to exacerbate migraine through inflammatory pathways. Special emphasis is placed on the role of physical exercise, which has demonstrated anti-inflammatory and neuromodulatory effects. Regular aerobic activity can reduce migraine frequency, duration, and intensity by lowering inflammatory markers and improving vascular and hormonal balance. Other supportive strategies include dietary modifications, probiotic supplementation, and patient education within a biopsychosocial framework. A multidisciplinary and personalized approach, combining medication, exercise, nutrition, and education, offers the most promise for long-term migraine management and improved quality of life.